A NEW SPECIES OF DALBERGIA (LEGUMINOSAE) FROM MALAY PENINSULA - Bambang - Sunarno; Hiroshi - Ohashi (REINWARDTIA, 2002)
SUNARNO, BAMBANG & OHASHI, HIROSHI. 2002. A new species of Dalbergia (Leguminosae) from Malay Peninsula. Reinwardtia 12(1): 117–119. ? A new species, Dalbergia johoriensis from the Malay Peninsula is described. It is close to D. rostrata and D. havilandii but readily distinguished by the grooved midrib beneath, flowers with narrower standard and wings and style hairy in the lower part.